POWER OF ATTORNEY IN FAVOR OF A THIRD PARTY? - Savčić, Sanja Milan; Miščević, Nikolina B. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
According to the provision of Art. 75 of the Criminal Procedure Code, one or more defense attorneys may be selected and authorized by the defendant, or his legal representative, spouse, blood relative, adoptive parent, adoptive parent, brother, sister, foster parent and the person with whom the defendant lives in extramarital affairs, or any other permanent community of life, unless the defendant expressly objects. The aim of this provision is to provide professional defense to the defendant in criminal proceedings even when he is unable to provide it, but the relationship between the lawyer and the person authorized to conclude a contract with him is of a civil nature. Theory and jurisprudence have not dealt much with the legal qualification of this relationship or have done it only marginally. Moreover, the explanation of the judgment of the Supreme Court of Cassation on the solidary liability of the accused and the certain person (wife) opens a number of questions, which are the subject of research in this paper. First of all, what is the legal nature of the contract that a lawyer concludes with a client? Is it possible to conclude such a contract in favor of a third party? What is the legal nature of the subsequent granting of a power of attorney? If a contract is concluded in favor of a third party, what is the legal effect of such a contract concluded between the parties? Does the contract in favor of a third party also result in an obligation for a third party? Finally, bearing in mind that the solidary liability is not explicitly agreed, from what does the court derive that kind of liability?
Keywords: authorization, power of attorney, mandate contract, contract in favor of a third party, solidary liability.